Transverse electric surface waves in a plasma medium bounded by magnetic materials - Rashid Ali; Burhan Zamir; H.A. Shah (Results in Physics, 2018)
The transverse electric surface waves have been investigated with a plasma medium sandwiched between two ferrite films. The characteristic equations for the field components are derived and a dispersion relation is analytically obtained by using boundary conditions for the tangential field components. Numerical analysis shows the plots of effective wave index with surface wave frequency for different thicknesses and number densities of the plasma medium, and also for the different values of the dielectric constant of the ferrite films. Keywords: Transverse electric surface waves, Sandwich structures, Maxwell's equations, Dispersion relation